New insights on mind-muscle connection: motor imagery concomitant to actual resistance training enhances force performance - Piveteau, É.; Guillot, A.; Di Rienzo, F. (Journal of Science and Medicine in Sport, 2025)
Objectives Motor imagery (MI) practice has shown substantial benefits on force, but this was mostly demonstrated on force produced by isometric contractions in laboratory settings. Here, we tested a new type of MI intervention to improve force and power in expert athletes. Design CrossFit® athletes (n = 100) of national level were randomly assigned to experimental groups who completed a 5-weeks back squat training program (3 resistance training sessions/week, ~ 1h per week). A first group (n = 35) received instructions to perform kinesthetic MI of the concentric phase of the back squat concomitant to its physical execution (MICONCENTRIC). A second group (n = 35) performed kinesthetic MI of the eccentric phase concomitant to its physical execution (MECCENTRIC). A control group (n = 30) completed the same amount of physical training without engaging in MI (Control). Methods Performance was indexed from the 5 repetitions maximum (5 RM) squat workload before and after the intervention. Weekly, we assessed squat power using an accelerometer. Results MICONCENTRIC and MIECCENTRIC groups outperformed Control regarding pretest vs. posttest improvements in both 5 RM force and power (RP2 = 0.60, both p < 0.001). The MIECCENTRIC group also outperformed the MICONCENTRIC group for the 5 RM workload (RP2 = 0.27, p < 0.001). However, subjective evaluations revealed that athletes in the MIECCENTRIC group experienced higher effort perception and difficulty to complete the experimental task. Conclusions MI practice concomitant to physical training was efficient to improve force on a dynamic multi-joint exercise in expert athletes. Keywords Conditioning;Strength;Brain;visualization;performance;Rehabilitation